Effect of Instructional Package on Knowledge and Practices Regarding Care of the Patients with Intercoastal Drainage among Staff Nurses in Selected Hospitals - Sawant, Amruta R.; Gholap, Gayatri; Sawant, Suchita (Indian Journal of Nursing Sciences, 2024)
Introduction: Lungs are the vital organs for respiration. The lungs are covered by a double-layered serous membrane called pleura. The space between the pleura contains pleural fluid which helps in lubrication and prevents friction between the lungs and chest wall. Intercostal drain is a flexible plastic tube that is inserted through the chest wall into the pleural space. It is used to remove air, fluid, and pus from the intrathoracic space. Apatient may require an intercoastal drainage system at any time when the negative pressure in the pleural cavity is disrupted, resulting in respiratory distress. Aims: The aim of the study was to assess the effect of instructional package on knowledge and practices regarding care of the patients with intercoastal drainage among staff nurses in selected hospitals. Materials and Methods: A descriptive evaluatory research approach with one group pre-test post-test research design was used for the study. The sample comprised 50 staff nurses who fulfilled the inclusion criteria, using non-probability convenient sampling technique. Data were analyzed using descriptive and inferential statistics. Results: We observed that knowledge and practices measured after instructional package was significant (P < 0.05). There were association of knowledge with age, department, and qualification and for practices association found with age and qualification, respectively. Conclusion: Instructional package was effective measured to improve knowledge and practices regarding care of the patients with intercoastal drainage among staff nurses in selected hospitals.